Propuesta de un enfoque para el desarrollo de software educativo intercultural - Mamani Vilca, Ecler (2019)
According some experiences, we could appreciate that the software developing process by using the cascade life cycle it is inappropriate for small and medium scale software. The software development for education implies the engineers and teachers collaboration. This paper presents a software development approach focused on and prototype and evolutive software. The development of educative software is oriented to articulate between the developer and teacher, where the language and culture are respected and use the Information and Communication Technologies. The proposal was evaluated by secondary level teachers of Abancay City and Apurímac Department where the 79% of them accept and gives their conformity to the proposal.